Curb your enthusiasm. Challenges to the development of lithium-based linkages in Argentina. (March 2021) - Obaya, Martín; López, Andrés; Pascuini, Paulo
Abstract: This paper contributes to the literature on resource-based development by analysing the opportunities and obstacles faced by linkage-development initiatives adopted in Argentina around lithium. A case study research has been designed that analyses two dimensions of the lithium-ion battery (LIB) global production network (GPN). Firstly, the dynamics of the lithium-ion battery GPN within which lithium is produced and consumed. Secondly, the multi-level governance scheme, shaped by a system of norms put in place by the federal and provincial governments, that regulates the access, exploitation and use of lithium in Argentina. The article finds that the development of forward linkages faces significant hurdles. The obstacles mainly arise from the lack of capabilities to produce LIBs in a competitive manner, since both the technology and markets are dominated by firms operating in a few Asian countries. Moreover, the normative frame in Argentina is not conductive for firms to localize lithium-processing activities in the country. The development of production backward linkages, although not unproblematic, is benefitted by pressures to raise the productivity levels of lithium exploitations and to improve the quality of lithium products; by the availability of location-specific capabilities; and by social and environmental domestic concerns which may create incentives for some technological solutions to be developed locally. The paper concludes that the effective development of resource based linkages would highly benefit from an aligned strategic vision among the relevant stakeholders of the system, including the federal and provincial governments, local and foreign firms, and the scientific community. Highlights: The promotion of linkages is a key goal of resource-based development strategies. Lithium-rich countries in South America have actively sought to promote linkages. The promotion of backward linkages has more potential and faces less significant obstacles. Linkages related to LIBs are constrained by the structure and technological dynamics of the GPN. Aligning the strategic vision of relevant stakeholders is a condition for creating local linkages.